Reproductive output of the ornamental shrimp Lysmata vittata (Stimpson, 1860) (Decapoda: Caridea) in wild populations and under different maturation diets - Santos e Almeida, Andréa; Barros-Alves, Samara de Paiva [UNESP]; Hirose, Gustavo Luis [UNESP]; Alves, Douglas Fernandes Rodrigues (Taylor & Francis, 2018)
Reproductive output parameters (fecundity and egg volume) of Lysmata vittata were examined in a population in northeastern Brazil. Effect of maturation diets on the reproductive output of these shrimp under laboratory conditions was evaluated. Reproductive output was estimated for 25 shrimp collected in the wild. Another 45 pairs of shrimp were used for diet experiments, 15 pairs per treatment (T1: industrialized food, T2: fresh food, T3: mixed diets). For wild population, mean fecundity and egg volume were differed between developmental stages of the eggs. Fecundity was significantly lower in the specimens subjected to T1 diet (267 ± 141 eggs) compared with shrimp from the wild population (393 ± 183 eggs). Egg volume was significantly lower in shrimp subjected to three diets tested compared with those from wild population. Egg loss during embryonic development in L. vittata may be caused by several factors (e.g. aborted development and maternal cannibalism). Fresh food proved to be important for improving reproductive output in L. vittata reared in culture. We emphasize the significance of improving nutritional value and palatability of diets to improve cultivation efficiency. Lysmata vittata can be used as a model organism for future studies aiming to improve the cultivation techniques for shrimp of the genus. Abbreviations PSH: protandric simultaneous hermaphroditism; ARS: artificial refuge structures; CL: carapace length; EV: egg volume; L: largest diameter of the egg; S: smallest diameter of the egg; T1: industrialized pellets; T2: fresh ingredients; T3: mixed diets; ANCOVA: analysis of covariancr; SD: standard deviation.
Keywords: Caridea; diets; Lysmatidae; ornamental; reproductive output